Conversations in a failing state - Lawrence, Patrick; Asian Human Rights Commission (Hong Kong : Asian Human Rights Commission, 2008)
Political and social conditions of Sri Lanka; observations of a journalist.
Keywords: Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Social conditions